1994
DOI: 10.1016/0021-9673(94)00928-7
|View full text |Cite
|
Sign up to set email alerts
|

29-Silicon NMR evidence for the improved chromatographic siloxane bond stability of bulky alkylsilane ligands on a silica surface

Abstract: 29-Silicon Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers)Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Applying NMR techniques, Scholten et al [104,105] could explain and provide evidence for the high chemical stability of these bulky phases in acidic eluents. Fig.…”
Section: Acidic Eluent Conditionsmentioning
confidence: 99%
“…Applying NMR techniques, Scholten et al [104,105] could explain and provide evidence for the high chemical stability of these bulky phases in acidic eluents. Fig.…”
Section: Acidic Eluent Conditionsmentioning
confidence: 99%
“…Indeed, Kirkland et al have shown that phases with isobutyl substituted C18 silane groups exhibit a longer lifetime in low-pH aqueous organic mobile phases than their conventional methyl substituted analogues [7]. In an earlier paper we provided 29Si solid-state NMR evidence for a decreased hydrogen bonding contribution of residual silanols to the ligand sil0xane bond of di-isobutyl-n-octadecylsilane 0021-9673/97/$17.00 Copyright © 1997 Elsevier Science B.V. All rights reserved PII S0021-9673(96)00765-0 ligands [8]. This was considered a result of the sterically protecting properties of the bulky side groups, hampering the siloxane bond hydrolysis by acidic mobile phases.…”
Section: Introductionmentioning
confidence: 99%
“…It was surmised that these silanols will be analyte accessible during chromatography. From Table 1 it can be inferred that 60% of all silanols of the phase Rx-C, 8 and 45% of all silanols of the phase SB-C~8 are not directly accessible for analytes during the chromatographic separation process. These percentages are probably minimum values, since larger analytes will have more difficulty penetrating the alkylsilane layer before possibly encountering a residual silanol.…”
Section: Introductionmentioning
confidence: 99%
“…The other is based on the same substrate but has been derivatized with bulky di-isobutyloctadecylsilane structures, which has proven to result in an increased stability under low pH conditions. Moreover, it was argued that the bulky side groups would increase the steric shielding of the underlying residual silanols by the silane ligand. Details on the relation between the 29 Si NMR signals of these ligand silanes and the observed increased low-pH stability have been published elsewhere . In order to obtain information on residual silanol concentration, mobility and solute accessibility, a combination of deuterium exchange in acetonitrile/D 2 O and 29 Si CP MAS NMR experiments was performed.…”
Section: Introductionmentioning
confidence: 99%